Spirituality as a Means of Adaptation to Life and Illness for Oncology Patients: A Scoping Review of Quantitative Studies between 2019 and 2025 - Bitēna, Daiga Katrīna (Journal of religion and health, 2026)
This scoping review examines the role of spirituality in helping oncology patients adapt to illness and life. An analysis of 49 quantitative studies from 2019 to 2025 revealed that positive manifestations of spirituality are linked to better mental health and improved adjustment to cancer and treatment. However, negative manifestations of spirituality are associated with poorer health outcomes and lower levels of adjustment. The lack of consensus regarding the definition and measurement of spirituality in oncology presents challenges. This study highlights the need to integrate structured spiritual care into cancer treatment.